Biodegradable sizing agents from soy protein via controlled hydrolysis and dis-entanglement for remediation of textile effluents. (1st March 2017) - Yang, Maiping; Xu, Helan; Hou, Xiuliang; Zhang, Jie; Yang, Yiqi
Abstract: Fully biodegradable textile sizes with satisfactory performance properties were developed from soy protein with controlled hydrolysis and dis-entanglement to tackle the intractable environmental issues associated with the non-biodegradable polyvinyl alcohol (PVA) in textile effluents. PVA derived from petroleum is the primary sizing agent due to its excellent sizing performance on polyester-containing yarns, especially in increasingly prevailing high-speed weaving. However, due to the poor biodegradability, PVA causes serious environmental pollution, and thus, should be substituted with more environmentally friendly polymers. Soy protein treated with high amount of triethanolamine was found with acceptable sizing properties. However, triethanolamine is also non-biodegradable and originated from petroleum, therefore, is not an ideal additive. In this research, soy sizes were developed from soy protein treated with glycerol, the biodegradable triol that could also be obtained from soy. The soy sizes had good film properties, adhesion to polyester and abrasion resistance close to PVA, rendering them qualified for sizing applications. Regarding desizing, consumption of water and energy for removal of soy size could be remarkably decreased, comparing to removal of PVA. Moreover, with satisfactory degradability, the wastewater containing soy sizes was readily dischargeable after treated in activated sludge for two days. In summary, the fully biodegradable soy sizes had potential to substitute PVA for sustainable textile processing. Graphical abstract: Highlights: Degradable textile size was developed from soyprotein to reduce effluent production. Performance of degradable soy protein size was comparable to commercial PVA size. Glycerol, the additive in soy protein size, is degradable, renewable, and low-cost.